S8 The National COPD Resources and Outcomes Project (NCROP): action plan achievement since 2007. (16th November 2010) - O'Reilly, J F; Pursey, N A; Roberts, C M; Stone, R A
Abstract : Introduction and Objectives: In 2007, 100 acute respiratory units participated in the NCROP, a randomised controlled study to assess whether reciprocal peer review could facilitate service improvement. We identified themes in desired improvements and evaluated success in meeting action plan aims. Methods: Units were paired and randomised into intervention or control arms (54:46). Intervention teams undertook reciprocal peer review in 2007 and documented action plans for service improvement. In 2010, intervention units self-assessed their progress in achieving action plans. Qualitative responses were analysed using a grouped themes approach to derive action plan themes. Results: Data were received from 41 of 54 intervention units (76%). The Abstract S8 Table 1 shows the distribution of themes and action plan outcomes. Conclusions: Action plan themes related predominantly to development of multi-disciplinary teams across primary and secondary care and to specialist service provision. Most aims were fully achieved in a third of units and partially achieved in a similar number. Palliative care plans were less prevalent although at least partially successful in two thirds. Overall change was greater than in the 1 year assessment of the NCROP audit 2008.1